The use of AHP and rank correlation methods for determining the significance of the interaction between the elements of a transport system having a strong influence on traffic safety - Podvezko, Valentinas; Sivilevičius, Henrikas (Transport, 2013)
A system of road transport involves vehicles, roads, traffic participants and freight that therefore closely interact. The interaction between these material elements takes place in an external environment. The process of transportation is aimed at achieving some positive results, which could increase the efficiency of the Transport System (TS). However, negative effects such as a high accident rate cannot be avoided. The road accident rate is determined by the properties of the material elements of the TS and the parameters of their interaction. Their impact on the traffic accident rate cannot be determined by a planned experiment. They also cannot be compared quantitatively, because their units of measurement are different. The paper presents a detailed description of nine types of the interaction between TS elements belonging to three various levels. The data was given to 16 transport engineering specialists as a questionnaire for expert evaluation. The paper offers a logical control methodology for filling in the questionnaire based on the Analytic Hierarchy Process (AHP) and the sequence of calculations of the consistency of expert estimates in the process of determining the weights of the investigated interactions. The Kendall's coefficient of concordance has been used for calculating the weights assigned to the criteria by a group of experts and estimating the consistency of the ranks based on them. Finally, the paper presents a new method for evaluating expert judgements with reference to the use of the correlation analysis of ranks and weights. The significance of the calculated pairwise correlation coefficients has been validated by the Student's t-test and lowest value thus allowing us to consider that the expert opinions about the impact of the interaction of TS elements on the traffic accident rate are consistent.First Published Online: 24 Dec 2013